Are you ready for the challenge? Social Media Health Challenges for behaviour change - Saboia, Inga (2020)
Challenges are one of the most common strategies used by Opinion Leaders on Social Media to engage users. They are often found in different areas; in the Health field, the use of challenges is growing, namely through initiatives aiming at eating behaviour change. Instagram is considered to be one of the most used Social Media applications to develop these initiatives, allowing Opinion Leaders to communicate and engage with their online followers. Despite this scenario, little is known regarding how Health Challenges are being used and what is their impact on behaviour change. Previous research has already shown how Opinion Leaders use Instagram to promote eating behaviour change. The purpose of this paper is to conceptualize, describe and discuss Social Media Health Challenges, aiming to analyse Instagram challenges on healthy eating. The study was organized in two phases: the first one is a literature review based on Prisma method that supported the conceptualisation of Social Media Challenges and the design for the second phase where Social Media Health Challenges of Opinion Leaders, such as Nutritionists, Health Lifestylers and Patient Opinion Leaders (POLS) were analysed. Results showed that most of the challenges are promoted by Patient Opinion Leaders and Health Lifestylers. Followers adhere to Social Media Health Challenges related to weight loss, engaging with Opinion Leaders. The psychological-cognitive components (such as habits, motivation, and self-control) were found in the analysed challenges, and Instagram is one of the used tools to promote these Initiatives. These results point to new paths regarding future research on other behaviour change online initiatives.